The Implementation of Enhanced Microgrid using Mayfly Algorithm based PID Controller - Murali, M; Sekhar, A Hema (ITEGAM-JETIA, 2025)
Micro grids, comprised of distributed generation units, are designed to function independently of the main grid. To ensure stable operation in isolated mode, precise control of system is essential. Common challenges faced by standalone microgrids include maintaining stability of the system with balancing the load and generation from renewable energy sources and preventing fluctuations.  Primary objective of paper to develop and execute an auxiliary controller capable of regulating system within a networked microgrid environment. Intermittent nature of renewable energy sources can lead to fluctuations in system frequency and power flow variations in tie line. To mitigate these challenges and balance the nonlinear output from renewable sources, Mayfly Algorithm (MA)-optimized Proportional-Integral-Derivative (PID) controller is proposed and implemented. Validation results demonstrate that the proposed MA-PID controller effectively regulates system in response to varying load demands and renewable energy sources.